Lattice and magnetic effects on a d-d excitation in NiO using a 25 meV resolution X-ray spectrometer - Ishikawa, Daisuke; Haverkort, Maurits W.; Baron, Alfred Q. R. (Journal of the Physical Society of Japan, 2017)
We investigate the behavior of a d-d transition in NiO using a new x-ray spectrometer with 0.025 eV resolution at 15816 eV, and via ab-initio ligand field theory calculations. The transition at ∼1.7 eV energy transfer is measured at temperatures between 20 and 800 K, at a momentum transfer |Q| = 6.52 Å−1. Fine structure is clearly observed at 20 K. As temperature is increased, the excitation shifts to lower energy and broadens. We explain the energy shift as being related to thermal expansion and to magnetism. The broadening is well fit considering thermal fluctuations of the Ni-O bond length, with a scale factor found to be in reasonable agreement with calculation.